Balance de Energía durante El Ciclo de un Cultivo de Trigo - Silvina, Righetti; María, Gassmann; Jesús, Gardiol (Ciência e Natura, 2007)
Estimation of sensible, latent and ground heat fluxes were obtainedwith data observed at a micromet-eorological tower stated at wheat cropplot in the area of Balcarce (Buenos Aires province). The Monin-Obukhovsimilarity approximation was used for turbulent fluxes. The periodcorresponds to the 2000-2001 growing season.